1995
DOI: 10.1016/s0006-3495(95)80151-7
|View full text |Cite
|
Sign up to set email alerts
|

Selective adhesion of functional microtubules to patterned silane surfaces

Abstract: We show that microtubule polymers can be immobilized selectively on lithographically patterned silane surfaces while retaining their native properties. Silane films were chemisorbed on polished silicon wafers or glass coverslips and patterned using a deep UV lithographic process developed at the Naval Research Laboratory. Hydrocarbon and fluorocarbon alkyl silanes, as well as amino and thiol terminal alkyl silanes, were investigated as substrates for microtubule adhesion with retention of biological activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 38 publications
1
71
0
Order By: Relevance
“…One is that the photoisomerization induced a change in the interaction between the monolayer surface having positively charged amino groups and microtubules being rich in (1) (2) (4) (3) the negatively charged carboxylate groups. 52 The other one is that the photoresponsive monolayer affects to the activity of kinesin.…”
Section: Resultsmentioning
confidence: 99%
“…One is that the photoisomerization induced a change in the interaction between the monolayer surface having positively charged amino groups and microtubules being rich in (1) (2) (4) (3) the negatively charged carboxylate groups. 52 The other one is that the photoresponsive monolayer affects to the activity of kinesin.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the first motility assays used naturally selfassembled actin filaments in the algae Nitella [72] and later artificially self-assembled F-actin paracrystals on lipid surfaces. [95] Early [4,30] and later work [90] demonstrated that microtubules adhere strongly to amine-terminated surfaces while retaining the ability to act as substrates for kinesin-coated beads. The critical issue of microtubule deactivation has also been addressed through stabilization with taxol [96] or glutaraldehyde.…”
Section: Surface Effectsmentioning
confidence: 99%
“…Nonetheless, an early study [30] demonstrated confinement of the movement of kinesin-coated beads on microtubules that had been pre-aligned in a flow field and immobilized on aminosilane patterns. More recently, microfabricated electrodes and flow fields were used to transversally align filaments.…”
Section: Lateral Confinement Of Movement Formentioning
confidence: 99%
“…Currently, the in vitro motility assay is also used to determine the feasibility of constructing motor protein-based artificial biomachines, for which actin-myosin or MT-kinesin systems are considered promising building blocks. [8][9][10][11][12][13][14][15][16] New classes of devices including nanoscale molecular shuttles, 17,18 surface-imaging processes, 19 force measurements 20 and lab-on-a-chip devices 21 have been developed using knowledge obtained through the in vitro motility assay. To improve the organizational hierarchy of motor protein-based systems with emergent functions similar to those observed in natural systems, several active self-organization (AcSO) techniques have been developed.…”
Section: Introductionmentioning
confidence: 99%